2003
DOI: 10.1590/s0100-72032003000500006
|View full text |Cite
|
Sign up to set email alerts
|

Efeitos da isoflavona sobre os sintomas climatéricos e o perfil lipídico na mulher em menopausa

Abstract: RESUMOObjetivo: avaliar os efeitos da isoflavona, do gérmen da soja, sobre os sintomas climatéricos e o perfil lipídico na mulher em menopausa. Métodos: foi conduzido estudo prospectivo, com 50 mulheres em menopausa, divididas em: G1, usuárias de isoflavona (60 mg/dia) (n=25), e G2, placebo (n=25). Os critérios de inclusão foram FSH >40 mUI/mL e presença de fogachos. Foram excluídas as vegetarianas, fumantes, asiáticas, portadoras de doenças gastrointestinais e usuárias de terapia de reposição hormonal. No seg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 27 publications
(55 reference statements)
0
1
0
3
Order By: Relevance
“…As expected, significant amounts of different forms of isoflavones (mg/100 g) were found in the raw material used to prepare the sweet biscuit that used the soy by-product (okara). Esteves & Monteiro (2001) and Nahás et al (2003) state that the main isoflavones found in soybeans and their derivatives are daidzein, genistein and glycitein, which are present with various forms of glycosidic conjugates, depending on the extension of processing or fermentation. However, in the experimental sweet biscuit, no isoflavone was detected.…”
Section: Resultsmentioning
confidence: 99%
“…As expected, significant amounts of different forms of isoflavones (mg/100 g) were found in the raw material used to prepare the sweet biscuit that used the soy by-product (okara). Esteves & Monteiro (2001) and Nahás et al (2003) state that the main isoflavones found in soybeans and their derivatives are daidzein, genistein and glycitein, which are present with various forms of glycosidic conjugates, depending on the extension of processing or fermentation. However, in the experimental sweet biscuit, no isoflavone was detected.…”
Section: Resultsmentioning
confidence: 99%
“…A Terapia de Reposição Hormonal (TRH) é recomendada e considerada a mais eficaz, mas tem uma baixa incidência de uso, no qual cerca de 70% das mulheres que fazem a terapia abandonam no primeiro ano (NAHÁS et al, 2003). Um dos principais motivos é o sangramento irregular, também, a utilização desse tipo de tratamento, assim como com qualquer medicamento, necessita de acompanhamento, caso ocorra efeitos colaterais ou análise de interação medicamentosa, além do TRH ser contraindicado para muitas mulheres.…”
Section: Glycine Maxunclassified
“…Em estudo realizado por Nahás et al [28] , no qual participaram 50 mulheres com sintomas de climatério, 25…”
Section: Fitoterápicosunclassified